Internationalisation - real options, knowledge management and the uppsala approach - Casson, M.; Gulamhussen, M. A. (The Challenge of International Business, 2004)
Scandinavian literature on the internationalization strategy of a firm emphasizes the incremental and sequential nature of both the export process and the foreign direct investment process (see, for example, Johanson and Vahlne, 1977; Johanson and Wiedersheim-Paul, 1975; Strandskov, 1986). Firms acquire experience of one foreign market before entering the next: they do not enter all major markets at the outset. In this way they benefit from the lessons learnt in the early stages of expansion and avoid making too many big mistakes. There are two other theories, however — namely internalization and globalization — which seem to imply that, on the contrary, firms will internationalize in a single discrete step involving simultaneous entry into all markets. This conflict between the theories is more apparent than real, however. This chapter shows that the theory of organizational learning implicit in the Scandinavian approach in fact complements these other approaches, by highlighting factors which they omit. A formal model is presented which clarifies these complementarities and so enriches all three areas of theory. This chapter is an attempt to show the relevance of the real option analysis in the internationalization process.